Developing a conceptual influence diagram for socio-eco-technical systems analysis of biofouling management in shipping – A Baltic Sea case study. (September 2021) - Luoma, Emilia; Nevalainen, Lauri; Altarriba, Elias; Helle, Inari; Lehikoinen, Annukka
Abstract: Ship hulls create a vector for the transportation of harmful non-indigenous species (NIS) all over the world. To sustainably prevent NIS introductions, the joint consideration of environmental, economic and social aspects in the search of optimal biofouling management strategies is needed. This article presents a multi-perspective soft systems analysis of the biofouling management problem, based on an extensive literature review and expert knowledge collected in the Baltic Sea area during 2018–2020. The resulting conceptual influence diagram (CID) reveals the multidimensionality of the problem by visualizing the causal relations between the key elements and demonstrating the entanglement of social, ecological and technical aspects. Seen as a boundary object, we suggest the CID can support open dialogue and better risk communication among stakeholders by providing an illustrative and directly applicable starting point for the discussions. It also provides a basis for quantitative management optimization in the future. Graphical abstract: Unlabelled Image Highlights: We present a multi-perspective systems analysis of ships' biofouling management. The analysis is based on a literature review and expert knowledge. The result is a conceptual influence diagram based on a narrative review. The CID reveals the entanglement of social, ecological and technical aspects. The CID can support risk communication and provide basis for a quantitative tool.